REGIONAL LEVIES IN SPECIAL AUTONOMY PROVINCE: A CASE STUDY OF EXECUTIVE REVIEWS ON REGIONAL REGULATIONS - Badri Hasan Sulaiman; Muslem Abdullah (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2021)
In implementing Special Autonomy, various provinces in Indonesia compete to increase their Regional Levies. These efforts have encouraged the governments to create regulations that can add value to their provinces. However, these regulations sometimes experience disharmony and asynchronous with the higher regulations, both in terms of contents and technically. This issue has resulted in an increasing number of Regional Regulations being annulled or revised after being evaluated by the Ministry of Home Affairs. At least 7500 Regional Regulations since 2002, originating from all regencies/cities and provinces in Indonesia, have been evaluated by the Ministry of Home Affairs. Nearly half of these Regional Regulations were annulled because they contradicted the principles of the formation. It is assumed that this number will continue to rise with the increasing legislative process in the regions. Abstrak: Dalam upaya pelaksanaan otonomi khusus, berbagai provinsi di Indonesia bersaing dalam upaya peningkatan retribusi daerahnya masing-masing. Hal ini telah mendorong provinsi-provinsi untuk membuat peraturan (regulasi) yang dapat mendatangkan nilai tambah bagi provinsinya. Peraturan tersebut kadangkala mengalami ketidakharmonisan dan ketidaksinkronan dengan regulasi yang lebih lebih tinggi baik dari segi materi muatan maupun dari segi teknis pembuatannya. Hal ini mengakibatkan meningkatnya jumlah peraturan daerah yang dibatalkan atau yang perlu di revisi kembali setelah diuji oleh Departemen Dalam Negeri. Hingga saat ini, Depdagri telah mengevaluasi sedikitnya 7500 perda sejak 2002, yang berasal dari seluruh kabupaten/kota dan provinsi di Indonesia. Dari jumlah tersebut, hampir setengah dari jumlah perda tersebut dibatalkan karena bertentangan dengan prinsip pembentukan perda. Jumlah tersebut diasumsikan akan terus bertambah seiring dengan semakin meningkatnya proses legislasi di daerah. Kata Kunci: Retribusi Daerah, Peraturan Daerah, Eksekutif Review.